Above the eye, a fish tied to a mirror of water moves: Una fe provisional (1992-2012) by Luis Arturo Guichard - Arroyo Carvajal, Yordan (2025)
The purpose of this article is to show a critical approach to the collected poetry (1992-2012) of the Mexican-from Salamanca poet Luis Arturo Guichard. For this purpose, we find key points of relationship with texts by other authors and question certain approaches made by critics about his work. According to our opinion, his poetry should not be pigeonholed only in the theme of migrations, but there are aesthetic traces that go beyond, an understandable matter from a philosophical approach, such is the case of the importance of certain Heraclitus fragments in the work of this author. It is concluded that the work studied here consolidates an architectural puzzle from intelligent poetry that, although different in each of his five books, retains a classical and post-modern imprint linked to Guichard’s professions at the University of Salamanca.